Méthodes d’apprentissage du latin à l’Université : entre tradition et innovation - Béatrice Bakhouche; Eugénie Duthoit (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Teaching methods specially designed for teaching Latin have existed ever since the Renaissance. We will start with a historical presentation of learning approaches so as to highlight continuity and change. We will then present our project, which is to transform a paper-based approach into an e-learning approach.